Nanoparticles: A Hope for the Treatment of Inflammation in CNS - Zhu, Feng-Dan; Hu, Yu-Jiao; Yu, Lu; Zhou, Xiao-Gang; Wu, Jian-Ming; Tang, Yong; Qin, Da-Lian; Fan, Qing-Ze; Wu, An-Guo (Frontiers in Pharmacology, 2021)
Neuroinflammation, an inflammatory response within the central nervous system (CNS), is a main hallmark of common neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and amyotrophic lateral sclerosis (ALS), among others. The over-activated microglia release pro-inflammatory cytokines, which induces neuronal death and accelerates neurodegeneration. Therefore, inhibition of microglia over-activation and microglia-mediated neuroinflammation has been a promising strategy for the treatment of neurodegenerative diseases. Many drugs have shown promising therapeutic effects on microglia and inflammation. However, the blood–brain barrier (BBB)—a natural barrier preventing brain tissue from contact with harmful plasma components—seriously hinders drug delivery to the microglial cells in CNS. As an emerging useful therapeutic tool in CNS-related diseases, nanoparticles (NPs) have been widely applied in biomedical fields for use in diagnosis, biosensing and drug delivery. Recently, many NPs have been reported to be useful vehicles for anti-inflammatory drugs across the BBB to inhibit the over-activation of microglia and neuroinflammation. Therefore, NPs with good biodegradability and biocompatibility have the potential to be developed as an effective and minimally invasive carrier to help other drugs cross the BBB or as a therapeutic agent for the treatment of neuroinflammation-mediated neurodegenerative diseases. In this review, we summarized various nanoparticles applied in CNS, and their mechanisms and effects in the modulation of inflammation responses in neurodegenerative diseases, providing insights and suggestions for the use of NPs in the treatment of neuroinflammation-related neurodegenerative diseases.